English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-09-20 02:30:42 · 2 answers · asked by Robert M 2 in Science & Mathematics Mathematics

2 answers

let x = e^(2z)

dx = 2 e^(2z) dz then intergand becomes:

1/2*dx/(sqrt(1-x^2)) --> this integrates to 1/2*arcsin(x) = 1/2*arcsin(e^(2z))

2007-09-20 02:45:44 · answer #1 · answered by nyphdinmd 7 · 0 0

☻ start with exp(2z) = sin x;

2007-09-20 09:49:27 · answer #2 · answered by Anonymous · 0 0

fedest.com, questions and answers